THE REGIONAL LIBRARY SYSTEM AS A FACTOR OF THE STUDENTS SOCIALIZATION - Yulia Kosintseva (Вестник Северо-Кавказского федерального университета)
The article describes the main aspects of the Information Space of the library as a factor ofsocialization students in the region. Specificity of the socialization of students is seen primarily as the creation of conditions for the development of professional competencies of young people.